DESCRIPTION OF SARCOPENIA FREQUENCY AND ANALYSIS OF AGREEMENT BETWEEN THE CALF CIRCUMFERENCE AND THE EUROPEAN CONSENSUS FOR SARCOPENIA DIAGNOSIS IN ELDERLY - Silva Tavares, Graziela Morgana; Schopf, Pâmela Pissolato; Manfredini, Vanusa; Duarte De Moraes, João Feliz; Valle Gottlieb, Maria Gabriela (Pensar a Prática, 2016)
This study aimed to describe the frequency of sarcopenia and verify the agreement between instruments for diagnosis. This a cross-sectional study, where we used the algorithm proposed by the European Consensus Sarcopenia (EWGSOP), calf circumference (CC), muscle mass and body mass index. 167 elderly were evaluated with a mean age of 68.03 ± 6.12 years. The elderly frequency diagnosed by EWGSOP sarcopenia and CC was as follows: 40 (24.0%) and 15 (9.0%). A low degree of agreement between CC and the EWGSOP (P = 0.101) was found. However, these instruments due to the low financial cost and easy applicability are important auxiliary tools for the screening and diagnosis of sarcopenia in elderly.